Innovation System and Efficiency : A Bibliometric Review - Jianglin, Jiang; Rossazana Ab-Rahim, Ab-Rahim; Rosita, Hamdan (Association Cuadernos de economia, 2023)
Doing a bibliometric analysis of published literature using data from Scopus, this study seeks to provide light on the present status of research in the area of innovation systems and efficiency. The study finds possible areas of collaboration among researchers, organisations, and institutions by examining authors, research institutions, published articles, and research trends. The results of this study have important practical and policy ramifications, especially for decision-makers who want to develop andput into practice regulations that encourage innovation and boost productivity. The study's findings can help businesses and organization’s by pointing them in the direction of best practices and methods for enhancing the effectiveness of their innovationsystems. The study can also help programs for education and training that aim to improve innovative systems and efficiency by fostering knowledge and skill development. Finally, the study can offer insightful information on potential future research directions in the area of innovation systems and efficiency, enabling scientists to spot areas that still require more research. In conclusion, this study offers a thorough and current evaluation of the body of research on innovation systems and effectiveness. In especially for politicians, corporations, organization’s, and educators striving to improve innovation systems and efficiency, the practical and policy implications of the findings show the potential impact of this study on the outcomes in terms of innovation and efficiency.